HETEROGLOSSIA: ANOTHER SFG-BASED APPROACH TO TREATMENT OF WORD ORDER AS A MEANS FOR EXPRESSING MODALITY IN VIETNAMESE - Hiep, Nguyen Van (VNU Journal of Foreign Studies, 2020)
The paper first introduces heteroglossia – a development of Systemic Functional Grammar (SFG) in Hallidayan Systemic Functional Linguistics (SFL) school before suggesting possible uses of heteroglossia in present-day studies of language, with particular focus on the role of word order in sentences of Vietnamese, a typical isolating language. The change of word order is considered a means for expressing modality, as shown in several interesting examples in Vietnamese, which proves that SFG and heteroglossia as its variant is an effective approach for exploring the role of word order in Vietnamese.